Individual, yet collective voices: polyphonic poetic memories in contemporary Ukrainian literature. Issue 1 (2nd January 2020) - Achilli, Alessandro
ABSTRACT: This article analyzes polyphonic memory in recent works by Serhii Zhadan and Marianna Kiianovs'ka, two leading contemporary Ukrainian writers. Before focusing on Zhadan and Kiianovs'ka, the author analyzes some excerpts from poems by other contemporary writers in which memory is thematized at the crossroads of individual and collective remembering. In his latest collections, Zhadan has shown a tendency to shape his poetic world around a lyrical subject keen to collect human voices and memories with the aim of preserving them from oblivion. Kiianovs'ka's 2017 collection Babyn Iar: Holosamy consists of memory fragments expressed by the various voices that constitute its collective subject, the victims of the 1941 Babyn Iar tragedy. In spite of the difference between these two models of poetic polyphony, the former conveyed through the mediation of a lyrical subject and the latter directly expressed by individual voices, the author here argues that Zhadan's and Kiianovs'ka's recent poetry successfully links the singularity of individual memory to the collective experience. He also argues that polyphonic poetic memory can be read as a strategy to overcome the opposition between the "populist" and "modernist" approaches to literature that has marked the self-perception of Ukrainian literature since the early twentieth century.